EXPLORING THE GENETIC AND CLINICAL OVERLAP BETWEEN EHLERS-DANLOS SYNDROME, AUTISM SPECTRUM DISORDER, AND ADHD: A COMPREHENSIVE REVIEW - Agata Zapałowska; Michał Bielecki; Kamil Kondracki; Anna Bieda; Monika Kondracka; Wojciech Kozłowski; Milena Szczepańska (International Journal of Innovative Technologies in Social Science, 2025)
Background: Neurodevelopmental disorders, including Autism Spectrum Disorder (ASD) and Attention-Deficit/Hyperactivity Disorder (ADHD), manifest early in life and are characterized by impaired functioning in different life domains. A group of genetic tissue disorders known under the name Ehlers-Danlos Syndrome (EDS) also manifest themselves in early childhood. Recent research points to a possible genetic and symptomatic link between EDS and neurodevelopmental disorders. This review focuses on similar manifestations and co-occurrence of the disorders mentioned above. Objective: This review investigates the prevalence and significance of comorbid ASD and ADHD in individuals with EDS. Additionally, the genetic and symptomatic connections shared by those conditions are worth exploring, knowing that they could pave the way for joint diagnostic and treatment approaches. Methods: A systematic literature review was conducted using databases such as PubMed, Cochrane Library, Web of Science, and Google Scholar. Selected studies were chosen based on their focus on the prevalence of ASD and ADHD in EDS patients, genetic or neurobiological links, and statistical analyses of comorbid rates Results: The prevalence of ADHD in individuals with EDS is significantly higher than in the general population; according to available data, nearly half of EDS patients meet the diagnostic criteria for ADHD. A similar occurrence has been found in individuals diagnosed with EDS - they have a significantly higher chance of being diagnosed with ASD. Shared gene variations between EDS and ASD/ADHD related to synaptic function and neural development have been identified by several genetic studies. The results indicate the possibility of common neurodevelopmental pathways between those conditions. Furthermore, both EDS and ASD/ADHD present with shared symptoms such as joint hypermobility, proprioceptive issues, and autonomic dysfunction. Conclusion: Numerous reports highlight the higher than-in-population comorbidity rates of ASD and ADHD in EDS patients. This emphasizes the need to implement routine screening and improve the management of individuals suffering from these conditions. Further research into the genetic and neurobiological connections can help introduce new interventions focused on the complexity of the problem and improve results in patient care and quality of life.